Role of the Bulky Aryloxy Group at the Non‐Peripheral Position of Phthalocyanines for Dye Sensitized Solar Cells. Issue 1 (20th July 2016) - Tejerina, Lara; Martínez‐Díaz, M. Victoria; Nazeeruddin, Mohammad K.; Grätzel, Michael; Torres, Tomas
Abstract: To date β‐aryloxy‐substituted designs have led to the best results in phthalocyanine‐sensitized solar cells (Pc‐SCs) because of their low aggregation properties. By incorporating the bulky semiflexible 2, 6‐diphenylphenoxy group at three α‐positions of the Pc, different regioisomers were separated by column chromatography and their photovoltaic performance was thoroughly studied. Efficiencies in the range of 1.9–4.1 % were found, thus demonstrating the importance of the steric interaction between the substituents and the semiconductor surface, also in the case of bulky semiflexible substituents. It was discovered that regioisomers which presented greater steric hindrance around the anchoring group, had lower adsorption densities, and, consequently, lower short‐circuit photocurrents ( J sc ) and efficiencies. Abstract : A selective performance : Photovoltaic performance of carboxyZnPc substituted with bulky semiflexible aryloxy groups at the non‐peripheral positions (see structure) is clearly influenced by the steric hindrance of the substituents with respect to the semiconducting surface. Thus, regioisomers with substituents oriented towards the carboxylic acid anchoring group turn out to have lower adsorption densities, and, consequently, lower short‐circuit photocurrents ( J sc ) and efficiencies.